2022
DOI: 10.3390/ijgi11120603
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Potential Zone Mapping: Integration of Multi-Criteria Decision Analysis (MCDA) and GIS Techniques for the Al-Qalamoun Region in Syria

Abstract: One of the most critical processes for the long-term management of groundwater resources is Groundwater Potential Zonation (GWPZ). Despite their importance, traditional groundwater studies are costly, difficult, complex, and time-consuming. This study aims to investigate GWPZ mapping for the Al-Qalamoun region, in the Western part of Syria. We combined the Multi-Influence Factor (MIF) and Analytic Hierarchy Process (AHP) methods with the Geographic Information Systems (GIS) to estimate the GWPZ. The weight and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 95 publications
1
5
0
Order By: Relevance
“…Marine sandstone and Sediment have been given the highest weightage for maximum groundwater permeability, followed by the rest of the features (Table 7). Fieldwork revealed that the riverine and marine sedimentary environment gives greater water recharge to the aquifer, and this is consistent with many related studies (Barua et al 2021;Alrawi et al 2022;Ghadeer 2022).…”
Section: (Li)supporting
confidence: 89%
See 1 more Smart Citation
“…Marine sandstone and Sediment have been given the highest weightage for maximum groundwater permeability, followed by the rest of the features (Table 7). Fieldwork revealed that the riverine and marine sedimentary environment gives greater water recharge to the aquifer, and this is consistent with many related studies (Barua et al 2021;Alrawi et al 2022;Ghadeer 2022).…”
Section: (Li)supporting
confidence: 89%
“…Groundwater in Syria is one of the crucial foundations for supporting the process of economic and social development, especially in the post-war phase (Baba et al 2021;Alrawi et al 2022). The development of a multi-criteria spatial model that enables reliable demarcation of regions constitutes an urgent research gap at the level of creating flexible and sustainable groundwater management strategies in Syria in the face of current and future challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The artificial neural network (ANN) and fuzzy rule-based (FR) models require a substantial amount of input prediction data [ 67 ], such as the location of dam sites and ponds, in order to accurately predict rainwater harvesting (RWH). Conversely, multi-criteria decision analysis (MCDA) models, including the analytic hierarchy process (AHP), do not rely on input data as they utilize logical classification of factors to assign weights and ratings to input parameters for the purpose of delineating the RWH map [ [68] , [69] , [70] ]. In this study, the Analytic Hierarchy Process (AHP)-based MCDA [ 71 ] and GIS-based Soil Conservation Service Curve Number (SCS–CN) were employed to generate a potential RWH map of the study area.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, vegetation cover influences various water cycle processes: runoff, evapotranspiration, and infiltration [110,111]. Alrawi [112] reported that agricultural lands decelerate surface runoff and increase water infiltration. The LC map of HQW was provided by GEOSURV (Figure 9a).…”
Section: Environmental Criteriamentioning
confidence: 99%
“…One of the essential procedures in evaluating the accuracy of any model is the validation of results, where models might not be advantageous from a scientific perspective without verification [112]. In reviewing the literature, different methodologies are utilized to validate the RH maps, such as correlation analysis, segmentation accuracy assessment, receiver operating characteristic curve, and sensitivity analysis [4,20,31,44,56].…”
Section: Validation Of the Wlc And Ahp Modelsmentioning
confidence: 99%